Analysis of Performance Management Systems in Military - Setiawan Nur Prakoso Utomo; Reza Fathurrahman (Universitas Sultan Ageng Tirtayasa, 2022)
This article uses literature studies and interviews to find out the extent to which the performance management systems and practices commonly found in non-military public sector organizations are also applied within a military organization with the Yonzipur 9/LLB Divif 1 Kostrad case study. To this end, in the first stage the researcher conducted an analysis of twenty selected articles related to the topic of performance management to find out the key elements in public sector performance management in general. Furthermore, researchers conducted interviews with a number of speakers from both the military and public sector human resources experts to enrich the results of the analysis. In general, military organizations as well as public organizations in general have performance management systems and practice a number of key elements of performance management systems including, among others: Performance planning, determination of performance targets, implementation, performance feedback, rewards and recognition. However, military organizations have their own peculiarities as implications of the existence of a rigid command system and organizational culture. This research is expected to be able to contribute to increasing understanding of performance management practices in military organizations while knowing the uniqueness of Kostrad as a military organization compared to other public sector organizations.